Does a biomedical research centre affect patient care in local hospitals?. Issue 1 (December 2017) - Lichten, Catherine; Marsden, Grace; Pollitt, Alexandra; Kiparoglou, Vasiliki; Channon, Keith; Sussex, Jon
Abstract Background Biomedical research can have impacts on patient care at research-active hospitals. We qualitatively evaluated the impact of the Oxford Biomedical Research Centre (Oxford BRC), a university-hospital partnership, on the effectiveness and efficiency of healthcare in local hospitals. Effectiveness and efficiency are conceptualised in terms of impacts perceived by clinicians on the quality, quantity and costs of patient care they deliver. Methods First, we reviewed documentation from Oxford BRC and literature on the impact of research activity on patient care. Second, we interviewed leaders of the Oxford BRC's research to identify the direct and indirect impacts they expected their activity would have on local hospitals. Third, this information was used to inform interviews with senior clinicians responsible for patient care at Oxford's acute hospitals to discover what impacts they observed from research generally and from Oxford BRC's research work specifically. We compared and contrasted the results from the two sets of interviews using a qualitative approach. Finally, we identified themes emerging from the senior clinicians' responses, and compared them with an existing taxonomy of mechanisms through which quality of healthcare may be affected in research-active settings. Results We were able to interview 17 research leaders at the Oxford BRC and 19 senior clinicians at Oxford's acute hospitals. The research leaders identified a wide range of beneficial impacts that they expected might be felt at local hospitals as a result of their research activity. They expected the impact of their research activity on patient care to be generally positive. The senior clinicians responsible for patient care at those hospitals presented a more mixed picture, identifying many positive impacts, but also a smaller number of negative impacts, from research activity, including that of the Oxford BRC. We found the existing taxonomy of benefit types to be helpful in organising the findings, and propose modifications to further improve its usefulness. Conclusions Impacts from research activity on the effectiveness and efficiency of patient care at the local acute hospitals, as perceived by senior clinicians, were more often beneficial than harmful. The Oxford BRC contributed to those impacts.